Detection and genetic characterization of group A rotavirus strains circulating among children with acute gastroenteritis in Japan - Tung G.P. (2014)
A total of 603 fecal specimens collected from July 2005 to June 2006 from children with acute gastroenteritis, encompassing five different localities in Japan, were screened for group A rotavirus by reverse transcription-PCR. It was found that 117 fecal specimens (19.4%) were positive for group A rotavirus. Rotavirus infection was detected continuously from November to June, with the highest prevalence in April. The G (VP7 genotypes) and P (VP4 genotypes) types were further investigated. The predominant genotype was G1P[8] (70.1%), followed by G3P[8] (17.9%), G9P[8] (6.8%), and G2P[4] (2.6%). A number of unusual G1P[4] combinations were also detected during this study period. A novel nomenclature for G1 is proposed, in which worldwide rotavirus G1 strains are classified into 11 lineages with 17 sublineages. A wide range of amino acid substitutions (up to 34) in VP7 that are specific for G1 lineages and sublineages were identified. Interestingly, only short amino acid motifs located at positions 29 to 75 and 211 to 213 of VP7 defined correctly the phylogenetic G1 lineages and sublineages. Examination of the deduced sequences of antigenic regions of VP7 also revealed multiple particular amino acid substitutions that correlated with the phylogenetic G1 lineages and sublineages. Of note, at least three distinct clusters of rotavirus G1 isolates were cocirculating in the Japanese pediatric population studied. Copyright © 2007, American Society for Microbiology. All Rights Reserved.